2017
DOI: 10.1146/annurev-polisci-051215-023141
|View full text |Cite
|
Sign up to set email alerts
|

State Building in the Middle East

Abstract: This review examines state building in the Middle East from a long-term, historical perspective. The Middle East's early transition to settled agriculture meant the region was home to many of the most sophisticated and best-developed states in the ancient world. As Middle Eastern states emerged from Late Antiquity, their fiscal and bureaucratic capacity enabled institutional forms not possible in Europe, including reliance on slave soldiers for the state military elite as well as state control of land that cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…This key assumption finds support in the historical comparative works looking at the societies of the Middle East and Western Europe. For example, in an overview of state building literature in the Middle East, Blaydes (2017) importantly makes the relevant connections between…”
Section: Historical Recordsmentioning
confidence: 99%
“…This key assumption finds support in the historical comparative works looking at the societies of the Middle East and Western Europe. For example, in an overview of state building literature in the Middle East, Blaydes (2017) importantly makes the relevant connections between…”
Section: Historical Recordsmentioning
confidence: 99%
“…61 With this in mind, a number of historians have demonstrated that the Muslim state was shaped through the interaction of the political and religious dynamics of the Middle East, 62 a position endorsed by Blaydes. 63 This argument shows how a range of factors and time periods, including the pre-Islamic, Islamic, colonial and postcolonial, shaped contemporary forms of political organisation. 64 Moreover, norms may be comprised of the residue of previous experience that remains in the historical narratives of the state or the public consciousness.…”
Section: Colonial Legacies and Regional Forcesmentioning
confidence: 99%
“…In considering the importance of bureaucratic institutions we must remember the impact of competing visions of nomoi that shape the construction of such institutions. While the importance of religion and Islamic law in shaping institutional development cannot be ignored, 84 we must also note that the importance of tribal values, which go some way to regulating contemporary life albeit requiring regulation within the context of the contemporary state. 85 This position is also held by Wael Hallaq, who stresses how political leaders are required to operate within the context that they inherited, which demonstrates a 'cumulative history of past action and specific manners of conduct' .…”
Section: Legitimacy and Neopatrimonialismmentioning
confidence: 99%
“…A shift to property rights, for instance, could not have occurred without a state, “a specialized form of organization, to specify, adjudicate and enforce property rights” (North, , p. 64). Indeed, the early Islamic state, that of the Umayyads and Abbasids, played a significant role investing in and organizing the economy (Brett, ; Frantz‐Murphy, 2007a,b; Sijpesteijn, ; Blaydes, ). The imperial administration in the early centuries of Islamic rule implemented several policies and presided over cultural processes that benefitted the economy.…”
mentioning
confidence: 99%
“…The new regional states in the Middle East and North Africa, successor states that followed the dismemberment of the empire and reconstituted themselves as independent units with state capacity, benefitted from these policies. The term state capacity refers to the power of the state to discharge its responsibilities and efficiently organize the economy, extract resources, collect taxes in equitable manner, distribute the benefits accrued to society, defend its citizens, invest in, and organize economic activities (Besley & Persson, ; Blaydes, ; Dincecco, ). The question at hand is to demonstrate how did the successor‐states by maintaining the benefits obtained during the Empire period in the post‐Empire period, save on the costs involved in state formation and in building state capacity (Bosworth, ; Spuler, ).…”
mentioning
confidence: 99%